2001
DOI: 10.1021/bi010536c
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Immunological Evolution of Antibody 28B4

Abstract: In an effort to gain greater insight into the evolution of the redox active, catalytic antibody 28B4, the germline genes used by the mouse to generate this antibody were cloned and expressed, and the X-ray crystal structures of the unliganded and hapten-bound germline Fab of antibody 28B4 were determined. Comparison with the previously determined structures of the unliganded and hapten-bound affinity-matured Fab [Hsieh-Wilson, L. C., Schultz, P. G., and Stevens, R. C. (1996) Proc. Natl. Acad. Sci. U.S.A. 93, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 33 publications
2
64
0
6
Order By: Relevance
“…4). This ''lock-and-key'' binding mode (22) of the affinity-matured antibody versus ''induced-fit'' binding mechanism (23) in the germ-line antibody was also observed in the antibodies 48G7, AZ28, and 28B4 (19,24,25) and further supports the hypothesis that the structural plasticity of germ-line antibodies is a critical factor in the ability of the immune system to evolve antibodies that bind many distinct chemical structures.…”
Section: Comparison Of the Antibody-combining Site In The Germ-line Andsupporting
confidence: 66%
See 1 more Smart Citation
“…4). This ''lock-and-key'' binding mode (22) of the affinity-matured antibody versus ''induced-fit'' binding mechanism (23) in the germ-line antibody was also observed in the antibodies 48G7, AZ28, and 28B4 (19,24,25) and further supports the hypothesis that the structural plasticity of germ-line antibodies is a critical factor in the ability of the immune system to evolve antibodies that bind many distinct chemical structures.…”
Section: Comparison Of the Antibody-combining Site In The Germ-line Andsupporting
confidence: 66%
“…The binding properties (K d and k off ) of 7G12 Fab, germ-line Fab, and all of the mutants with NMP were measured by surface plasmon resonance on a Biacore 3000 biosensor following the published methods (19). BSA was conjugated with NMP and immobilized on a research grade CM5 sensor chip (Biacore).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent crystallographic and thermodynamic analyses of both germline and mature Ab-Ag complexes have suggested that the Ab repertoire can be further enhanced at the tertiary structural level (7,14,18,19,34,35). The present study provides an elegant correlation of CDR conformational versatility in a germline Ab with its multispecificity.…”
Section: Discussionmentioning
confidence: 74%
“…In the case of germline mAbs 28B4, 48G7, and AZ28, conformational rearrangement of CDRH3 has been shown to facilitate hapten binding. However, none of these studies have associated conformational flexibility of CDRs with degenerate specificity (14,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation constant K D , the dissociation rate constant k off , and the association rate constant k on of the Ab-Fl complexes were determined by using surface plasmon resonance on a Biacore 3000 biosensor (Biacore, Uppsala, Sweden) following published methods (38). Briefly, BSA was conjugated with Fl and immobilized on a research-grade CM5 sensor chip.…”
Section: Methodsmentioning
confidence: 99%